A mulch in time ... - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
ILCA (International Livestock Centre for Africa) has conducted trials in the Ethiopian high lands on the tree legume Sesbania sesban which shows much promise in being able to sustain or increase the organic matter content and fertility of the soil...